Searching for Africa in Brazil power and tradition in candomblé - Capone, Stefania 1960-; Lyall Grant, Lucy; Capone, Stefania 1960-; Capone, Stefania 1960- (Durham, N.C. [u.a.] Duke Univ. Press, 2010)
The messenger of the gods : Exu in Afro-Brazilian religions -- The spirits of darkness : Exu and Pombagira in Umbanda -- The religious continuum -- Reorganizing sacred space -- Contesting power -- Exu and the anthropologists -- In search of lost origins -- Which Africa? which tradition?
The messenger of the gods : Exu in Afro-Brazilian religions -- The spirits of darkness : Exu and Pombagira in Umbanda -- The religious continuum -- Reorganizing sacred space -- Contesting power -- Exu and the anthropologists -- In search of lost origins -- Which Africa? which tradition?
Includes bibliographical references (p. [297]-310) and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Cults -- Brazil; Blacks -- Brazil -- Religion; Cults -- Brazil; Blacks -- Religion -- Brazil; Candomblé (Religion); Gods, Afro-Brazilian